2020
DOI: 10.3389/fmicb.2020.00322
|View full text |Cite
|
Sign up to set email alerts
|

Metatranscriptomics Reveals Antibiotic-Induced Resistance Gene Expression in the Murine Gut Microbiota

Abstract: Antibiotic resistance is a current and expanding threat to the practice of modern medicine. Antibiotic therapy has been shown to perturb the composition of the host microbiome with significant health consequences. In addition, the gut microbiome is known to be a reservoir of antibiotic resistance genes. Work has demonstrated that antibiotics can alter the collection of antibiotic resistance genes within the microbiome through selection and horizontal gene transfer. While antibiotics also have the potential to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…In addition, metatranscriptomic studies focused on RNA sequencing (RNA seq) also allow functional changes to be discovered to decipher what can affect antibiotic resistance gene expression after exposure to antibiotics. They can also study changes in the virulence factors of specific pathogens and epigenomic studies of some neoplastic conditions ( Sharma et al, 2010 ; Korry et al, 2020 ; Auld et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, metatranscriptomic studies focused on RNA sequencing (RNA seq) also allow functional changes to be discovered to decipher what can affect antibiotic resistance gene expression after exposure to antibiotics. They can also study changes in the virulence factors of specific pathogens and epigenomic studies of some neoplastic conditions ( Sharma et al, 2010 ; Korry et al, 2020 ; Auld et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al [ 101 ] found that levofloxacin could induce transformation and promote the spread of drug-resistant E. coli . Misuse of antibiotics alters gut microbiota homeostasis and promotes horizontal transfer of resistance genes in vivo [ 98 ]. The antimicrobial treatment enhances the selection of resistant strains and results in an increase in the resistance gene pool, which ultimately raises the risk of spreading resistance genes [ 102 ].…”
Section: Factors Influencing the Transfer Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…Antibiotics. As a huge reservoir of antibiotic resistance genes, the human gut microbiome may be involved in the spread of resistance genes to pathogens [98]. External intake of antibiotics or resistance genes may affect the resistance changes of intestinal flora.…”
Section: Factors Influencing the Transfer Of Antibiotic Resistance Genesmentioning
confidence: 99%
“…Furthermore, the traditional best hit approach would fail to predict the novel metallo beta lactamase genes, indicating the sensitivity and robustness of machine learning approaches in ARG surveillance (Arango-Argoty et al, 2018). DeepArg has been widely used in several studies that have revealed correlations of total ARGs with anthropogenic impacts in natural environments (Collins-Fairclough et al, 2018;Chen et al, 2019b;Zeng et al, 2019), increased ARGs in murin gut under antibiotic treatments (Korry et al, 2020), and reduction of ARGs in bioreactors upon ozone pre-treatment (Xia et al, 2020).…”
Section: Metagenomic Approaches For Resistome Surveillancementioning
confidence: 99%